Analisis Implementasi Kebijakan Pro Poor Budgeting pada Program Kartu Indonesia Pintar Terhadap Penerima Program Kartu Indonesia Pintar (Studi Kasus Mahasiswa S-1 Akuntansi Universitas Pembangunan Nasional “Veteran” Jawa Timur Angkatan 2021) - R. Rifqi Izzhulhaq; Sri Trisnaningsih (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to reveal the implementation of pro poor budgetting policy of Kartu Indonesia Pintar program in order to reach education equality. The method of the study is descriptive qualitative. The research was conducted at UPN Veteran East Java. The informans were those who gets the benefit of Kartu Indonesia Pintar program, the student of S-1 Acountant program year periode 2021. The data was collected by observation, detail interview, and documentation (the pictures of student's residences). The result of the study will reveal that the pro poor budgetting policy has been applied in Kartu Indonesia Pintar program toward students of S-1 acountant program, 2021; and it can be stated that it has reached out the right target. So, it is in accordance to the government's resposibility that is to give every citizenship equal right of having education in order to enrich the quality and the benefit of government support entirely.